Feeding and handling of dairy cattle: An integrative review - Wilamune, Nirodha Heshan; Jayasinghe, Madhura Arunoda; Gunawardena, Sajani Nuwandima; Samarasinghe, Chathuranga Hasithi (Journal of Pure and Applied Agriculture, 2023)
: Global cattle dairy sector has shown significant development during the past few years due to many improvements in some areas. Two of the major areas that have improved are; cattle nutrition, feed types and feeding systems & feeding frequency. Regarding the cattle nutrition, there were quite a few studies carried out to identify the contribution by each nutrient on milk yield and its properties. Some studies were conducted to investigate the impact on the milk yield and its properties by different sources of nutrients. Another area that has recently advanced is the feed types provided to the animals. Several studies have investigated the benefits as well as disadvantages of different feed types. Same as cattle nutrition, there were several research projects conducted to determine the impact of feeding systems and feeding frequencies on milk yield and its properties. For example, studies regarding impact of total mixed rations on milk properties were carried out worldwide.